Students’ “COVID-19” and “school” perceptions in the pandemic - Vural, Ömer F.; Başaran, Mehmet; Demirtaş, Zeynep; Karamanlı, Aynur R.; Bayrakcı, Cansu (Frontiers in Psychology, 2022)
This study aims to reveal high school students' perceptions of Covid-19 and schools in the pandemic process through metaphors. In the study, phenomenology research design based on qualitative research method was used. The study was carried out with the participation of 134 students at all grade levels from high school. The data were analyzed by content analysis. The metaphors were categorized according to their similarities and their frequency values were calculated. 76 metaphors and 8 categories about Covid 19 were reached and "flu", "prison" and "snake" are the metaphors that have the highest frequency values. They explained the metaphors by making associations with the disease, fast-spreading and damaging things. In the Covid-19 process, 78 metaphors and 8 categories were found out for the school. Based on the metaphors created by the students, suggestions were made depending on the research results. It was determined that students had negative perceptions about the Covid-19 pandemic and the school in this process, and it was suggested that this could be eliminated again with educational activities.